DEVELOPMENT OF ANDROID APPLICATION LEARNING MEDIA USING ISPRING SUITE 9 TO INCREASE STUDENT LEARNING MOTIVATION - Aida Azzahrah; Indra Adi Budiman; Yuyun Dwi Haryanti; Mahpudin Mahpudin (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
The purpose of this research is to develop an android-based learning media in thematic for grade IV elementary schools in Cikalong 1 to increase learning motivation. This research uses the type of research and development, the development model used in this research is ADDIE. The ADDIE development model has five stages namely, analysis, design, development, implementation, and evaluation. The result of the research on the development of the developed learning media obtained an average value of the level validated by material experts and media experts which was 87,05% with the valid category. The results of the questionnaire response from the teacher and 20 students obtained practicality of 91,25% and the result of the student's response questionnaire obtained a percentage of 92,12% and the result of the student motivation test percentage of 93%, meaning that the android application media attract students attention and increase students learning motivation.